2017
DOI: 10.15640/jges.v5n1a2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Suitability of Upland Rice for Adoption as Food Security and Poverty Alleviation Crop in Uganda

Abstract: This study was carried out in Uganda with the aim of developing a suitability map for upland rice crop based on physio-chemical soil properties and climatic factors. The analysis used physio-chemical variables of soil pH, Cation Exchange Capacity of the soils (CEC), Soil organic carbon (SOC), Digital elevation (DEM) and 19 bioclimatic variables. The physio-chemical suitability maps were derived using Geographical information system approach based on weighted overlay analysis in ArcGIS10.3, while the climate su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The projected distribution area for the species is basically the probability of habitat suitability niches, or the niche models generated by using MaxEnt software (Phillips et al ., 2006; Elith and Leathwick, 2009), which could be potentially used for forecasting distribution pattern of agricultural crops. Similar studies have been reported for invasive species (Lamsal et al ., 2018), rare trees (Deb et al ., 2017; Qin et al ., 2017) and cereal crops (Ojara et al ., 2017). In the current study, the MaxEnt models indicated large changes in climatic suitability across the agro-ecological zones, which is a crucial factor for the adaptability and distribution of crops.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The projected distribution area for the species is basically the probability of habitat suitability niches, or the niche models generated by using MaxEnt software (Phillips et al ., 2006; Elith and Leathwick, 2009), which could be potentially used for forecasting distribution pattern of agricultural crops. Similar studies have been reported for invasive species (Lamsal et al ., 2018), rare trees (Deb et al ., 2017; Qin et al ., 2017) and cereal crops (Ojara et al ., 2017). In the current study, the MaxEnt models indicated large changes in climatic suitability across the agro-ecological zones, which is a crucial factor for the adaptability and distribution of crops.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the MaxEnt models indicated large changes in climatic suitability across the agro-ecological zones, which is a crucial factor for the adaptability and distribution of crops. Therefore, monitoring crop habitat suitability dynamics is important in assessing their distribution path for sustainable production and future planning (Ojara et al ., 2017; Sharma et al ., 2018). In the current research, the models under all the three anthropogenic forcing of IPCC showed large variations, in terms of magnitude and space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation